PERWALIAN (HAK ASUH) ANAK YANG DIBERIKAN KEPADA AYAH AKIBAT PERCERAIAN (STUDI PUTUSAN NOMOR 355/PDT.G/2022/PN JKT.UTR) : Child’s Guardianship (Custodial Rights) Granted to The Father due to Divorce (Study on Verdict Number 355/PDT.G/2022/PN JKT.UTR) - Rehuel Natalia El; Yogo Pamungkas (AMICUS CURIAE, 2024)
Child’s guardianship given to whom due to a divorce is not strongly regulated, but child custody disputes are decided by courts based on children’s interests. The decision of District Court Number 355/Pdt.G/2022/PN Jkt.Utr decides that the father receives the guardianship of the three children. The issues in this article are whether the  judge's legal considerations in awarding custody of the kid to the father conform with Law Number 1 of Year 1974 on Marriage and Government Regulation Number 29 of Year 2019 on Terms and Procedures for Appointing Guardians and whether the guardianship (custodial rights) of the child is given to the father based on the best interest of the child according to best interests as outlined in Law Number 23 of 2002 on Child Protection, as revised by Law Number 35 of 2014. The judge's consideration is incorrect because it must be based on the interests of each child to achieve guardianship goals and be in line with the principle of the child's best interests. Girls should be assigned to mothers based on their interests in puberty, menstruation, physical changes, and feminine concerns. Women's faults as wives cannot be considered since a woman who is not good as a wife is not necessarily bad as a mother. It is preferable to grant the mother primary guardianship of daughters as long as the mother performs her tasks, duties, responsibilities, and obligations appropriately and fairly to protect the child's growth and best interests of the child.